Internalization of Universal Religious Values in Developing Religious Moderation in Parigi Moutong State Senior High Schools - muhammadismail; Sagaf S. Pettalongi; Mashuri, Saepudin (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2024)
This research discusses the Internalization of Universal Religious Values ​​in developing Religious Moderation in Torue State Senior High Schools. This research examines the process of internalizing universal religious values ​​in developing religious moderation and the impact of the results of internalizing universal religious values ​​in developing religious moderation at State Senior High School Torue. This research uses a qualitative approach, and data is collected through observation techniques, in-depth interviews, and written document analysis. The results of this research show that four values are internalized in State Senior High School 1 Torue, namely, the value of justice, the value of tolerance, the value of humanity, and the value of peace. The process of internalizing universal religious values ​​is carried out through several stages. The first stage is value transformation through awareness by understanding religious values. Next, the value transaction process involves direction, guidance, and examples for students to adhere to religious values. From the results of the transinternalization carried out, students have been able to apply the universal religious values ​​that are instilled, including in the implementation of policies or regulations made by the school, providing encouragement to students to practice good values ​​in their actions, following the good examples of the students and educators, as well as creating a harmonious environment in schools. The impact of internalizing religious values ​​plays an essential role in forming the character of moderate, tolerant students who respect religious diversity, respect their elders, are disciplined, are used to differences, are used to practicing worship, are close to friends, and are socially concerned.